Dé-penser l'économique sans Mauss et avec Polanyi - Sobel, Richard (L'Homme & la société, 2005)
Keywords: MAUSS, Marcel, 1872-1950

Y a-t-il une économie sartrienne ? - Kail, Michel; Sobel, Richard (L'Homme & la société, 2011)
RésuméEn dépit de l’absence d’un exposé économique systématique dans l’œuvre de Sartre, nous soutenons qu’il y a bien une économie sartrienne, même si celle-ci est encore à développer. Le statut que Sartre réserve à la « rareté » lui permet de faire un pas supplémentaire vers la critique de l’économisme par rapport à celui déjà effectué par Karl Polanyi, qui s’est contenté de récuser la confusion entretenue entre l’économique et sa définition formelle. La rareté, nous enseigne Sartre, ne saurait en effet être soumise au traitement de la raison instrumentale, mais considérée, ajoute-t-il, comme un fait humain dans l’histoire. Aussi, l’analyse économique ne doit-elle pas s’appuyer sur la notion de « nature » et la thématique de l’homme confronté à la nature, en l’occurrence « ingrate », mais articulée sur la notion de « monde » telle que la philosophie sartrienne l’élabore., Despite the absence of a systematic analysis of economics in Sartre’s work, we argue that there can indeed be said to be a Sartrean economics, even if it is one that still awaits development. The status which Sartre accords to the concept of Scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason, but considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man’s confrontation with a typically ungrateful Nature, but articulated through the concept of World as elaborated in Sartrean philosophy.
Keywords: SARTRE, Jean-Paul, 1905-1980; economic systems

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Keywords: POLANYI, Karl, 1886-1964; SARTRE, Jean-Paul, 1905-1980; economic systems; economism; scarcity; world